Kepemimpinan Etis Pada Institusi Pendidikan - Rahman, Abdul; Zaenuri, Lalu; rowi, siti (Institut Pemerintahan Dalam Negeri (IPDN), 2023)
One of the problems faced by the world of education lately is the decline in social life manners and moral ethics in the practice of school life. Various ethical violations that occur in school institutions highlight the important role of ethical leadership in school institutions. The seeds of ethical violations in schools if not eliminated will become habits and do not rule out the possibility of giving birth to leaders who are smart but do not have ethics and morals in managing ethical accountability. The purpose of this study was to elucidate ethical leadership in educational institutions. The research method used is a literature review method of literature study with a type of descriptive research. The findings show that the task of ethical leadership in educations is to enable students to develop confidence and appreciation for facts and skills. The approach used is to insert moral values in every rule of teaching facts and skills in every subject in school. Because if not, then one day there will arise in society smart leaders but do not live up to religious teachings.